Spiritual education as a subspecies of relational education? - Fraser-Pearce, Jo (British Journal of religious education, 2022)
Though the promotion of spiritual ‘development’ is statutory in state-maintained schools in England and Wales, it is neither clear what spirituality is nor how schools might educate in this area. In the literature, one finds an array of divergent conceptions of spirituality and spiritual education. There is, indeed, lack of agreement regarding whether spiritual education has any place in schools other than those of a religious character. Some argue that spirituality is beyond definition. I reject the notion that spirituality, and hence spiritual education, is beyond definition. I defend and develop Michael Hand’s ‘education in a spiritual activity’. I argue that spirituality concerns connectivity, or relationship, with the transcendent. This relational understanding of spirituality resembles existing accounts of spirituality as relational and underpins an account of spiritual education as relational education – again resembling existing accounts. However, I distinguish between relational education which concerns a wide range of relationships and spiritual education as a subspecies of relational education which specifically concerns relationship with the transcendent. I argue that reserving the term ‘spiritual’ for relationship with the transcendent would enable teachers and pupils to make the kinds of distinctions which are important in both spiritual education and the wider relational education.